Bertalanffy Model Reflects Growth Trajectory in Aseel Chicken - Kumar, Amit; Kumar, Sanjeev; Pandey, Manjari; Chaudhari, Chirag; Verma, Med Ram; Chandrahas; Chauhan, Anuj (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Aseel, a popular breed of native chicken, characterized by its pugnacity, fighting strength and royal gait is being used to create crosses for domestic chicken production. However, information on its growth models is scanty. An experiment was conducted to evaluate different non-linear models and to find out best fitting model in Aseel, being maintained at Central Avian Research Institute, Izatnagar, Bareilly. Data on body weights from 12-weeks of age to 20-weeks of age at biweekly intervals were recorded on a random bred single-hatched flock. Owing to the non-linear characteristic of growth, three non-linear models namely, Gompertz, Bertalanffy and Logistic models were evaluated. Goodness of fit for all the models were checked using coefficient of determination (R2), adjusted coefficient of determination (Adj-R2), mean square error (MSE), mean absolute error (MAE) and Akaike information criterion (AIC). The Bertalanffy model most accurately characterized the growth trend in males, females and pooled sex data. The study revealed that this model may be used to ascertain the average body weights in Aseel chicken under random mating. The investigation has generated baseline data on growth modelling of random bred groups and may be used in similar investigations on other native chicken breeds.